The Influence of Job Training and Work Motivation on the Work Performance of Bandar Lampung Primary Vocational School Teachers - Ardansyah, Ardansyah; Rakel Yoandri (International Journal of Economics, Business and Innovation Research, 2025)
Work performance is a crucial aspect in supporting the improvement of educational standards in schools, especially for teachers As the central force in the learning process. Two aspects that have an impact on teacher work performance are job training and work motivation. This study seeks to examine the connection between job training and work motivation on teacher performance at Bandar Lampung Main Vocational School. A quantitative approach utilizing multiple linear regression analysis was applied. The population consists of all Bandar Lampung Primary Vocational School teachers, with a sample of 30 teachers selected by implementing purposive sampling techniques. Questionnaires were distributed to respondents, then analyzed using data quality testing and hypothesis testing methods. The results of the analysis explain that job training and work motivation simultaneously influence teacher work performance. Between these two variables, job training makes a greater contribution, although both complement each other in supporting performance improvement. Providing suggestions to schools to strengthen relevant job training programs and improve strategies to motivate teachers, in order to create a quality learning environment and support educational achievement the optimal one.